2013
DOI: 10.1093/geront/gnt117
|View full text |Cite
|
Sign up to set email alerts
|

Computer Proficiency Questionnaire: Assessing Low and High Computer Proficient Seniors

Abstract: The CPQ and CPQ-12 are useful tools to gauge computer proficiency for training and research purposes, even among low computer proficient older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(128 citation statements)
references
References 12 publications
2
123
3
Order By: Relevance
“…The concept of assisting the older adult through the use of technology to avail of healthcare has enormous potential. Boot et al (2015) endorsed the social connectedness and importance of engaging with family and friends whereby information technology can be of huge assistance. The demographic shift caused by the worldwide growth of the older population coincides with the dramatically altering and redefining how people communicate and relate to each other.…”
Section: Use Of Technology To Cope With Health and Social Burden In Omentioning
confidence: 99%
“…The concept of assisting the older adult through the use of technology to avail of healthcare has enormous potential. Boot et al (2015) endorsed the social connectedness and importance of engaging with family and friends whereby information technology can be of huge assistance. The demographic shift caused by the worldwide growth of the older population coincides with the dramatically altering and redefining how people communicate and relate to each other.…”
Section: Use Of Technology To Cope With Health and Social Burden In Omentioning
confidence: 99%
“…Participants were also classified as being at risk for social isolation based on the following criteria: they did not work more than 5 h per week (including volunteer work) and did not attend a senior center or another type of formal organization more than 10 h per week. They were recruited as part of the PRISM clinical trial examining the effect of a computer intervention on well-being (ClinicalTrials.gov Identifier: NCT01497613; see also [15]). The data presented here are baseline data before intervention administration for the clinical trial.…”
Section: Participantsmentioning
confidence: 99%
“…With respect to age, data from the Pew Internet and American Life Project showed that only 53 % of adults 65 and older use the Internet as compared to 97 % of [18][19][20][21][22][23][24][25][26][27][28][29] year olds [13]. Nevertheless, research suggests that older adults can use and integrate computers into their lives [14], be proficient users [15], and be just as active online as younger users [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Participants were instructed to imagine that they had been given a computer system developed specifically for use by older adults, along with the appropriate personalized training for its use. The description was based on a system used in a randomized clinical trial designed to assess the impact of a computer intervention on the well-being of seniors with minimal computer experience (ClinicalTrials.gov Identifier: NCT01497613) [16,17]. …”
Section: Methodsmentioning
confidence: 99%